Comprehensive Assessment of Business Activity of a Commercial Organization - MISHULINA, Olga Vladimirovna; BARANOVA, Natalya Arkadyevna; VINOGRADOVA, Natalya Pavlovna; GORELOVA, Natalya Sergeevna (Journal of Advanced Research in Law and Economics, 2019)
The article substantiates the need for a comprehensive approach to the assessment of business activity and its practical application in a commercial organization. The methodological basis of the study is the works of representatives of classical and modern economic schools. The research methods include general and special scientific methods (quantitative and qualitative methods of strategic analysis). The dual nature of the business activity (as a process and as a goal) is revealed, its types are characterized, and methodological approaches to its assessment in a commercial organization are systematized. In the implementation of an integrated approach to the assessment of business activity on the example of a commercial organization, a system of indicators is formed in terms of types of business activity, which are represented by relative values and have a unidirectional character. The conducted complex assessment characterizes all types of activity of an organization and determines levers of influence on its business activity. The proposed algorithm is universal; it does not depend on branch accessory, the size of the commercial organization, and its organizational and legal form.